2003
DOI: 10.1080/1071576031000105643
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition andIn VitroEvaluation of Antioxidant Effect of Free Volatile Compounds FromSatureja montanaL.

Abstract: As a part of an investigation of natural antioxidants from Dalmatian aromatic plants, in this paper we report a study of the antioxidant activity related to the chemical composition of savory free volatile compounds. Twenty-one compounds were identified in the essential oil without fractionation, representing 97.4% of the total oil. The major compound was phenolic monoterpene thymol (45.2%). Other important compounds were monoterpenic hydrocarbons p-cymene (6.4%) a nd gamma-terpinene (5.9%)and oxygen-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 17 publications
3
64
1
1
Order By: Relevance
“…Additionally, camphor was determined as the major compound of S. visianii Silic (Bezic et al, 2009;Dunkic & Bezic, 2008;Vidic et al, 2009). It is possible to increase the number of these kinds of examples as the following: isomenthone for S. boliviana (Dambolena et al, 2009;Hatami et al, 2011;Senatore et al, 1998), thymoquinone (Grosso et al, 2009b;Mastelic & Jerkovic, 2003;Palavra et al, 2011;Taborsky et al, 2012), geraniol (Cavar et al, 2008;Mastelic & Jerkovic, 2003;Radonic & Milos, 2003b), and carvacrol methyl ether (Serrano et al, 2011;Skocibusic & Bezic, 2004) for S. montana.…”
Section: Volatiles (Terpenes)mentioning
confidence: 99%
“…Additionally, camphor was determined as the major compound of S. visianii Silic (Bezic et al, 2009;Dunkic & Bezic, 2008;Vidic et al, 2009). It is possible to increase the number of these kinds of examples as the following: isomenthone for S. boliviana (Dambolena et al, 2009;Hatami et al, 2011;Senatore et al, 1998), thymoquinone (Grosso et al, 2009b;Mastelic & Jerkovic, 2003;Palavra et al, 2011;Taborsky et al, 2012), geraniol (Cavar et al, 2008;Mastelic & Jerkovic, 2003;Radonic & Milos, 2003b), and carvacrol methyl ether (Serrano et al, 2011;Skocibusic & Bezic, 2004) for S. montana.…”
Section: Volatiles (Terpenes)mentioning
confidence: 99%
“…The final density of bacterial and yeast's inoculum was 5 x 10 5 . Suspensions of the molds were made in sterile saline and their turbidity was confirmed by viable counting in a Thoma chamber.…”
Section: Micro-well Dilution Assaymentioning
confidence: 99%
“…Also, it is used as choleretic, stimulant, digestive, antiseptic for gastrointestinal tract [2] and for the treatment of premature ejaculation [3]. A number of investigations justified traditional utilization and have confirmed various biological effects of this plant species namely, antioxidant [4,5], antibacterial [4,[6][7][8][9][10] and antifungal [11]. Satureja montana essential oil showed antiproliferative activity on human erythroleukemic K562 cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…carvacrol or thymol. Various techniques were used: 2,2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging assay [63,69,70,71,72], β-carotene bleaching test [68,70,72], thiobarbituric acid reactive species (TBARS) assay [67,69,73], ferric ion reducing antioxidant power (FRAP) assay [72], oxygen radical absorbance capacity assay [74] and method measuring the formation of hydroperoxydienes from linoleic acid [67]. With help of electron spin resonance (ESR) spectroscopy Fujisawa et al [75] found that eugenol and eugenol-related synthetic compounds possessed radical scavenging activity comparable with the activity of conventional antioxidants.…”
Section: Mutagenicity Anti-mutagenicity and Dna-protective Effectsmentioning
confidence: 99%